(3fWGb JWHjb GMcGe bGfhf GdJMcje ai eUQ (B: s (3OQGSI ebGQfI (B/ s - (3GMeO eMeO YHO GdHOjY TJGs; (3SejMI GdbdjhHis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2002)
(3GaJJMJ OQGSJj gPg HHGH JegjOj jJfGhd HYV GdeSGFd GdYGeI GdeJYdbI HfXGe GdJMcje heGgjJg , hWHjYJg GdbGfhfjI hJWhQg GdJGQjNj h GdCfhGY GdeNJdaI dg, Ke GfJgjJ Edi JbSje OQGSJj Edi KdGKI CHhGH eJJGdjI , jJMOK GdHGH GdChd ajgG Yf fWGb GdCTNGU GdPjf jMb dge GddLhA Edi GdJMcje ShGA CcGfhG CTNGU WHjYjjf Ch GYJHGQjjf h CgdjJge aj GdGJaGb Ydj GdJMcje , h eGgjI GdJMcje eJYOO GdCWQGa hGdUYhHGJ GdYedjI GdJj JhGLgg, CeG GdHGH GdKGfj abO JfGhdJ ajg ehVhYGJ GdJMcje ef MjK cjajI JMOjOgG hJYjjfgG hbGHdjJgG hYOe bGHdjJgG dCf Jchf eMdG ddJMcje , eY EHQGR HYV GdUhQ GdYedjI aj gPG GdTCf , hLGA CNjQG GdHGH GdKGdK dcj jJMOK Yf fWGb JWHjb CMcGe GdbGfhf GdeUQj ddJMcje ef MjK GdecGf hGdReGf , hGdbGfhf hGLH GdJWHjb Ydj ELQGAGJ GdJMcje hYdj ehVhY GdfRGY eMd GdJMcje hGdeTcdGJ GdYedjI GdJj JbY aj gPG GdTCf , eY GSJYQGV OhQ HYV GdeQcR h GdgjFGJ GdOGFeI ddJMcjes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2002s
(3HHdjhLQGajG(B: (3UaMGJ (B347-355s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJMcje aj GdbGfhf GdeUQis; (3GdJMcje aj GdbGfhf GdaQfSjs; (3GdWHjYI GdbGfhfjI ddJMcjes; (3CfhGY GdJMcjes; (3CgdjI GdGJaGb Ydi GdJMcjes; (3fWGb JWHjb CMcGe bGfhf GdJMcjes; (3GdbGfhf hGLH GdJWHjbs; (3eMd GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs